Assessing natural herd immunity to tick-borne encephalitis in Republic Sakha (Yakutia) - A. G. Dragomeretskaya (Sankt-Peterburg : NIIÈM imeni Pastera, 2019)
Tick-borne encephalitis (TBE) is a natural focal viral neuroinfection vastly spread in the mid-latitude climate zone of theEurasia. Lethal cases and disability related to TBE determine its high epidemiological significance as well as underlie undiminished attention to prevent it in endemic territories. At the same time, TBE epidemiologic features significantly differ in various geographic areas. Importantly, Republic Sakha (Yakutia) is not among TBE endemic areas in theRussian Federation. However, in the last decade an increased incidence of ixodic tick bites was registered in the Republic Sakha. A pattern of pathogen-specific population immunity is one of the most valuable criteria for assessing magnitude of epidemic process in TBE foci. Hence, our study was aimed at assessing natural herd immunity TBEV in Republic Sakha associated with elevated incidence of tick bite visits. Here, we analyzed the data regarding the rate of tick attacks in the period of 2001–2007 in Republic Sakha. Residents and individuals unvaccinated against TBEV in the city ofYakutskas well as various administrative regions were examined to record the peak incidence of tick attacks. It was found that a range of the administrative regions recording with registered of ixodic tick attacks and elevated incidence of tick bites was expanded. Moreover, the top incidence of tick bites was annually recorded in the south regions of the republic Aldanian, Neryungri, Olyekminsk, Leninsk, Khangalassky districts, city ofYakutskand its suburbs. Furthermore, TBEV-specific immunoglobulins were detected in 5.7±0.68% of the residents examined suggesting about contacts with the pathogen. In addition, the peak count of seropositive people (8.9±1.85%) was identified in Namsky district located in the central part of the republic. Overall, detection rate of TBEV-specific antibodies among general adult population (6.9±0.95%) was significantly higher compared to those observed in children (3.9±0.89%, р < 0.05). no significant differences in urban (5.8±1.12%) vs. rural population (5.63±0.84%) was found.